Health Information Needs of Tuberculosis Patients in Lagos State, Nigeria. Issue 4 (2nd October 2021) - Olayemi, Olalekan Moses; Abolarinwa, Shola Timothy
ABSTRACT: This study is aimed at identifying health information needs of tuberculosis (TB) patients, their preferred sources for receiving health information, and the factors influencing the choice source used. A descriptive cross-sectional study was the design adopted. The study population was TB patients older than 18 years old who were accessing health-care service in the Directly Observed Treatment (DOT) Center. A total of one hundred and ninety-eight (198) patients participated in the study and a questionnaire was used to collect the data. The data were analyzed using SPSS software. The findings of the study show that the health information needs of tuberculosis patients are as follows: prevention of tuberculosis (53.0%); causes of tuberculosis disease (48.1%); and drug information about the disease (47.6%). The outcome also revealed that the respondents chose medical doctors and nurses as the most preferred source of information, with accessibility as the main factor influencing the information source user. The study outcome demonstrated that tuberculosis patients acknowledge the need for health information to improve their health conditions. Therefore, health-care professionals should redirect their educational programs and efforts on educating the TB patients on the various types of information sources that could enhance their health conditions.